Covalent organic framework-based materials for energy applications - Wang, De-Gao; Qiu, Tianjie; Guo, Wenhan; Liang, Zibin; Tabassum, Hassina; Xia, Dingguo; Zou, Ruqiang (Energy & environmental science, 2021)
The excessive depletion of fossil fuels and consequent energy crisis combined with environmental issues call for inexhaustible, clean and renewable energy sources and environmentally friendly energy technologies, such as solar energy and novel electrochemical energy conversion and storage devices. Developing supporting platforms for energy conversion and storage ameliorating mass transfer and electron transfer has stepped into the center of the energy research arena. Covalent organic frameworks (COFs) are emerging crystalline porous materials linked via covalent bonding possessing flexible molecular design and synthetic strategies, high conjugated and modifiable structures, large surface area and porosity. Due to these merits, COFs have shown promising perspectives in energy applications including photocatalysis, electrocatalysis, supercapacitors, metal-ion/sulfur batteries, etc. This critical review imparts a comprehensive summary of the fast-developing COF field in terms of molecular design and subsequent synthetic strategies to prepare COFs with highly conjugated and modifiable structures and their applications in energy conversion and storage. Furthermore, challenges and perspectives according to previous contributions are also discussed for developing more efficient energy conversion and storage COF materials. It is anticipated that this review could boost further research enthusiasm for COF-based materials in energy applications. The recent progress in the synthesis and energy applications of the covalent organic frameworks has been elaborated in this review article.